ATTENTION AND CONCENTRATION ABILITIES, THE DIFFERENCE BETWEEN STUDENTS WHO HAD BREAKFAST AND STUDENTS WHO DIDN’T HAVE BREAKFAST IN UPTD SMA NEGERI 2 NGANJUK - Robertha Lutfi Andreani; Pauline Meryana (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Indonesia had the lowest position in cognitive skills and educational achievement according to the research of the Economist Intelligence Unit in 2014. Cognitive skills are the brain abilities to reach knowledges and understanding from experiences and information. Parts of cognitive domain are attention and concentration. Attention is the ability to focus on problems. Concentration is the ability to maintain the attention in the longer periode of time. The availibility of adequate nutrition can be achieved by consuming good and various foods, especially at the breakfast. This research aimed to study the difference of attention and concentration abilities between students who had breakfast and those who didn’t in UPTD SMA Negeri 2 Nganjuk. The subjective assessment used questionnaire and the objective assessment used Moca-Ina assessment. This was an analytic research with cross sectional research design applied to 42 eleventh grade students in UPTD SMA Negeri 2 Nganjuk. The sampling technique was Simple Random Sampling by distributing the questionnaire and performing Moca-Ina assessment grade students in UPTD SMA Negeri 2 Nganjuk. The data were processed with version 20 SPSS. The result showed that there were significant differences of the attention and subjective concentration abilities between students who had breakfast and students who didn’t have, based on the breakfast menus (p=0.012), breakfast calories (p=0.012), and breakfast time between who had breakfast at 06.00-06.59 AM and who didn’t have or had breakfast before 06.00 AM (p=0.004). Also, there were significant differences ot attention and objective concentration abilities among students who had breakfast and students who didn’t have (p=0.035) based on Moca-Ina assessment. The researcher could conclude that subjectively and objectively there were significant differences of attention and objective concentration abilities between students who had breakfast and those who didn’t. Respondents who had breakfast had better attention and concentration abilities than the ones who didn’t have.